2014
DOI: 10.1002/2013jd020611
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of interpolation techniques for the creation of gridded daily precipitation (1 × 1 km2); Cyprus, 1980–2010

Abstract: High-resolution gridded daily data sets are essential for natural resource management and the analyses of climate changes and their effects. This study aims to evaluate the performance of 15 simple or complex interpolation techniques in reproducing daily precipitation at a resolution of 1 km 2 over topographically complex areas. Methods are tested considering two different sets of observation densities and different rainfall amounts. We used rainfall data that were recorded at 74 and 145 observational stations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 81 publications
(94 reference statements)
1
35
0
2
Order By: Relevance
“…The method developed and tested by Camera et al (2014) to derive 1 9 1 km 2 daily gridded data sets of precipitation for Cyprus (1980Cyprus ( -2010 was applied. The method involves inverse distance weighting (IDW) to interpolate local events, while a combination of step-wise geographically weighted regression and IDW is used for large scale events.…”
Section: Gridding Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…The method developed and tested by Camera et al (2014) to derive 1 9 1 km 2 daily gridded data sets of precipitation for Cyprus (1980Cyprus ( -2010 was applied. The method involves inverse distance weighting (IDW) to interpolate local events, while a combination of step-wise geographically weighted regression and IDW is used for large scale events.…”
Section: Gridding Schemesmentioning
confidence: 99%
“…Hence, a simplified gridding scheme is developed. Thiessen polygons are established around each observational station and raster cells, from the 1 9 1 km 2 mask map of the gridded data sets (Camera et al 2014), are assigned to the different polygons. A scaling coefficient is calculated for each cell as the ratio between the mean annual rainfall (from observations 1980-2010) of the cell itself and the same value of the reference station, for the Thiessen polygon in which they fall.…”
Section: Gridding Schemesmentioning
confidence: 99%
“…Several spatial interpolation techniques such as inverse distance weighting (IDW) method, thin plate splines (TPS), trend surface analysis (including linear and polynomial regression), kriging and parameter elevation regression on independent slopes model (PRISM; Hutchinson, ; American Society of Civil Engineers (ASCE), ; Goovaerts, ; Hay et al , ; Daly et al , ) were used either independently or in a combination (Lin and Chen, ; Perry and Hollis, ; Camera et al , ) to generate gridded precipitation data in the last two decades. Among those, the deterministic IDW and the kriging methods with their respective variants are widely used both for the estimation of missing rainfall records and interpolation (Teegavarapu, ; Li and Heap, ; Ly et al , ; Yanto et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there has been little consensus on the relative superiority of these methods. For instance, Camera et al (2014) showed that different interpolation methods work better for local and large scale events (frontal or convective, etc. ).…”
Section: Introductionmentioning
confidence: 99%